SISTEM INFORMASI PELAYANAN JASA PADA MUTIARA LAUNDRY BERBASIS WEB - Mispuanda Mispuanda; Abdullah Abdullah; Ilyas Ilyas (Indragiri Islamic University, 2022)
One of the laundry businesses in Tembilahan is pearl laundry. Mutiara Laundry is a home-based business engaged in laundry services, which is located at Jl. Mount Daek in front of Lrg. Mataram II No. 10, Tembilahan City, Tembilahan, Indragiri Hilir Regency, Riau 2924. This laundry business has been running for the past few years. The problems that occur in this laundry business are difficulties in managing customer data, customer status data, transaction data, customer report data, washing service reports, and transaction reports. Then the problem is that the customer data management system is carried out manually and simply so that it is prone to income errors. To help manage the delivery of clothes that have been washed, then to facilitate the management of customer data through the website efficiently and provide convenience for both users and admins